Forecasting and Volatility Analysis of International Soybean Price From 2004 until 2014 - Novariandi, Panji Mario; Anggono, Achmad Herlanto (Journal of Business and Management, 2015)
Abstract.Soybean is the important commodity in Indonesia because its benefit. As the source of protein, soybean has been known and used for many food products such as tofu, tempe, ketchup, etc and most of the people of Indonesia tend to eat Tofu and tempe. The problem arises because Indonesia has become the importer of soybean and the international soybean price is volatile since 10 years. The price volatility can rise uncertainties and makes financial & strategic investment planning more difficult especially for soybean processor. Based on that problem, this paper is aimed to know the future price forecasting and the volatility of international soybean price in the next ten years. The result of this paper would be a baseline to hedge toward risk in soybean industry area. The sample of data is monthly international soybean price in periode of December 2004 until November 2014, counted for 120 observations. This financial time series data could be analyzed using Autoreggresive Integrated Moving Average (ARIMA) to show the result of the future price forecasting and volatily of soybean. There are three models tested here: ARIMA(1,1,0), ARIMA(0,1,1), and ARIMA(1,1,1). The result of this study shows that ARIMA(1,1,0) is the best model to forecast the international soybean price in the next ten years. Later in the forecasting result, there is strategy that can be recommended for soybean industry and importer to hedge against the volatility. The price predicted to rise sharply start from November 2016 until July 2018 so the soybean processor and importer especially should be prepared to establish forward futures contract before October 2016 for period November 2016 until November 2017 and December 2017 until July 2018 to lock the price against the upcoming trend that will come. After that the forward future contract shoukd be set once again to encounter with the upcoming trend which expected occur the next three years until August 2022.Â Keywords : soybean, volatility, future price, forecasting, ARIMA